THE EFFECTS OF OFFLINE TRACK CHANGES PEER-REVIEW AND ACHIEVEMENT MOTIVATION ON WRITING COMPETENCY - Kadek Cahyadi Putra (Edulingua: Jurnal Linguistiks Terapan dan Pendidikan Bahasa Inggris, 2022)
This experimental study investigated the effect of Offline Track Changes Peer-Review and achievement motivation toward students’ writing competency of the tenth grade at SMAN 1 UBUD. There were two variables examined. The independent variable was Offline Track Changes Peer-Review and moderator variable was achievement motivation. Dependent variable was writing competency. Posttest only control group design with 2x2 factorial arrangement was administered in this study. The population covered eight classes of the tenth grade and only four classes were taken as sample with 131 students. The data were collected using analytical writing rubric, achievement motivation questionnaire and anecdotal notes. Two way ANOVA and Tukeytest were administered to analyze the data. The result shows: (1) there was a significant effect of Offline Track Changes Peer-Review on students’ writing competency, (2) there was an interactional effect between Offline Track Changes Peer-Review and students’ achievement motivation on students’ writing competency, (3) there was a  significant difference of writing competency between high achievement motivated students taught by Offline Track Changes Peer-Review and high achievement motivated students taught by conventional strategy, and (4) there was a significant difference of writing competency between low achievement motivated students taught by Offline Track Changes Peer-Review and low achievement motivated students taught by conventional strategy.